Hierarchical carbon-coated acanthosphere-like Li4Ti5O12 microspheres for high-power lithium-ion batteries - Sha, Y.; Xu, X.; Li, L.; Cai, R.; Shao, Zongping (Elsevier SA, 2016)
In this work, carbon-coated hierarchical acanthosphere-like Li4Ti5O12 microspheres (denoted as AM-LTO) were prepared via a two-step hydrothermal process with low-cost glucose as the organic carbon source. The hierarchical porous microspheres had open structures with diameters of 4-6 µm, which consisted of a bunch of willow leaf-like nanosheets. Each nanosheet was comprised of Li4Ti5O12 nanoparticles that are 20 nm in size and coated by a thin carbon layer. When applied as the anode material for lithium-ion batteries (LIBs), the AM-LTO presented outstanding rate and cycling performance due to its unique morphologies. A high capacity of 145.6 mAh g-1 was achieved for AM-LTO at a rate of 40C (1C = 175 mAh g-1). In contrast, the sample synthesized without glucose as carbon source (denoted as S-LTO) experienced an obvious structural collapse during the hydrothermal reaction and presented a specific capacity of only 67 mAh g-1 at 1C, which further decreased to 14 mAh g-1 at 40C. Further morphological growth of the acanthosphere-like Li4Ti5O12 microspheres and their excellent performance as an anode in LIBs were also discussed in this work.